The Effectiveness of Corset use on Pain Scale Reduction in Post-Cesarean Section Mothers in the Acacia Ward at Eka Hospital Bekasi - Purwanti E.S, Yoyik Endang (Jurnal EduHealth, 2025)
This case study investigates the effectiveness of corset use as a non-pharmacological intervention in reducing pain among postpartum mothers following Cesarean Section (CS) in the Acacia Ward of Eka Hospital Bekasi. The patient initially experienced moderate-to-severe pain (scale 4–7), which progressively decreased to scale 2 within three days after corset application. In addition to the reduction in pain scores, the patient reported improved comfort, enhanced early mobilization, and decreased dependence on pharmacological analgesics. The corset provided compression and support to the incision area, stabilized abdominal muscles, reduced edema, and offered psychological reassurance, all contributing to decreased pain perception. These findings are consistent with existing literature highlighting the role of abdominal support devices as adjuvant therapy in post-CS pain management. This study suggests that corset use is a safe, practical, and effective intervention to complement pharmacological analgesia and improve patient recovery outcomes. Further research with larger samples and more rigorous study designs is recommended to strengthen the evidence base.